2011
DOI: 10.1088/1674-1056/20/2/025202
|View full text |Cite
|
Sign up to set email alerts
|

Propagation and interaction of ion—acoustic solitary waves in a quantum electron—positron—ion plasma

Abstract: This paper discusses the existence of ion-acoustic solitary waves and their interaction in a dense quantum electronpositron-ion plasma by using the quantum hydrodynamic equations. The extended Poincaré-Lighthill-Kuo perturbation method is used to derive the Korteweg-de Vries equations for quantum ion-acoustic solitary waves in this plasma. The effects of the ratio of positrons to ions unperturbation number density p and the quantum diffraction parameter He (Hp) on the newly formed wave during interaction, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 32 publications
(19 reference statements)
0
3
0
Order By: Relevance
“…In what follows, we numerically examine the foregoing results and effects of quantum diffraction as well as ion concentration and ion charge on the formation and behavior of an electrostatic DL by using the typical parameters of the degenerate plasmas found in the outer layers of dense astrophysical objects. [18,35] The electron and ion densities are assumed as n e0 6 × 10 28 cm −3 and n i0 0.2n e0 with Z i = 1. This leads to the average interparticle distance n −1/3 e0 2.5 × 10 −10 cm, H e 0.081, and H p 0.085.…”
Section: Numerical Analysis and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In what follows, we numerically examine the foregoing results and effects of quantum diffraction as well as ion concentration and ion charge on the formation and behavior of an electrostatic DL by using the typical parameters of the degenerate plasmas found in the outer layers of dense astrophysical objects. [18,35] The electron and ion densities are assumed as n e0 6 × 10 28 cm −3 and n i0 0.2n e0 with Z i = 1. This leads to the average interparticle distance n −1/3 e0 2.5 × 10 −10 cm, H e 0.081, and H p 0.085.…”
Section: Numerical Analysis and Discussionmentioning
confidence: 99%
“…Over the past few years, the studies of quantum plasmas in the framework of the hydrodynamic model have rapidly increased. This includes quantum ion-acoustic waves, and instabilities, [13,14] low frequency waves, and solitary structures in quantum dusty plasma, [15,16] solitons and shocks in quantum electron-positron-ion plasma, [17][18][19] and so on. The peculiarities of modeling nonlinear collective interactions in quantum plasmas have been pointed out recently in Refs.…”
Section: Introductionmentioning
confidence: 99%
“…[23][24][25][26][27][28][29][30][31][32] Many researchers have investigated the characteristics of IASWs described by both the KdV equation and the nonlinear Schrödinger equation (NLSE) to study the phenomenon observed in various laboratory and space plasma applications. [33][34][35][36][37][38][39][40] On the other hand, a large number of numerical simulation studies have been done for IASWs by using PIC method to check the theoretical results. [41][42][43][44] For instance, Kakad et al [42] have studied the characteristics of the ion-acoustic solitons such as amplitude, width and speed by both fluid and PIC simulations.…”
Section: Introductionmentioning
confidence: 99%